2016
DOI: 10.1038/tpj.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 polymorphism predicts progression-free survival in metastatic colorectal cancer patients treated with first-line bevacizumab-based chemotherapy

Abstract: We analyzed associations between CXCR4/CXCL12 single-nucleotide polymorphisms and outcomes in metastatic colorectal cancer (mCRC) patients who underwent first-line bevacizumab-based chemotherapy. A total of 874 patients were included in this study: 144 treated with bevacizumab and FOLFOX or XELOX (training cohort), 653 treated with bevacizumab and FOLFIRI or FOLFOXIRI (validation cohort A or B) and 77 treated with cetuximab- and oxaliplatin-based regimens (control cohort). One CXCR4 polymorphism (rs2228014) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…There are several studies which have also shown that SNP polymorphisms can be effective in the advancing and development of other cancers [ 47 , 48 ] and the present study. These studies indicate the importance of examining the association of the polymorphism of some genes with the progression of cancer.…”
Section: Discussionsupporting
confidence: 70%
“…There are several studies which have also shown that SNP polymorphisms can be effective in the advancing and development of other cancers [ 47 , 48 ] and the present study. These studies indicate the importance of examining the association of the polymorphism of some genes with the progression of cancer.…”
Section: Discussionsupporting
confidence: 70%
“…The results showed that MERTK and SYK were druggable according to the CIViC database (18,36,37). Gene variations in CXCR4, FCGR2A, MGAT4A, NCOA1, PIK3R1, RGS5, RRAS2 and SOD2 may be predictive markers or have targetable variations according to the PharmGKB database (16,3847). A total of 10 oncogenes ( CXCR4, ERG, FLT1, IGF1, KDR, LYN, MITF, PIK3CG, REL and SYK ), six tumor suppressor genes ( MITF, MAP3K1, MOB3B, NFKBIA, PRDM1 and SAMHD1 ) and one gene (CSF1R), belonging to neither oncogene or tumor suppressor gene categories, were identified, according to the oncoKB database.…”
Section: Resultsmentioning
confidence: 99%
“…A common CXCR4 polymorphism (rs2228014 C/C genotype) has recently been found to predict progression-free survival in metastatic colorectal cancer patients treated with first-line bevacizumab-based chemotherapy. 52 The nucleotide sequence of the CXCR4 gene and 350-bp upstream regulatory region from CT-2A and GL261 glioma genomic DNA was analyzed by Sanger sequencing of PCR-amplified products, but no CXCR4 mutations were identified in glioma cells that could alter their function or response to the treatments ( Figure 6 and Table 1).…”
Section: Cxcr4 Gene Mutation Analysis In Glioma Cellsmentioning
confidence: 99%